MicroRNA and mRNA Sequencing Analyses Reveal Key Hepatic Metabolic Pathways Responsive to Maternal Malnutrition in Full-Term Fetal Pigs. (7th June 2021) - Wang, Feng; Maltecca, Christian; Wang, Xiaoqiu; Odle, Jack; Xi, Lin
Abstract: Objectives: Maternal and infant undernutrition is highly prevalent in developing countries, leading to serious fetus/infant mortality, intrauterine growth restriction, stunting, and severe wasting. However, the effects of maternal undernutrition have generally focused on the reduced maternal nutrient supply to the fetus. The potential impairment of fetal metabolic pathways has not been well studied. Methods: Pregnant gilts (Landrace x Yorkshire x Duroc) received the NRC gestation diet with (n = 4) or without (n = 4) 50% intake restriction at insemination day and 70% for the following gestation period. Full term fetuses were obtained via C-section, two piglets were selected from each gilt in both groups and subject to hepatic tissue collection. MicroRNA and mRNA deep sequencing analysis was performed using the Illumina GAIIx system. The mRNA-miRNA correlation and associated signaling pathways were analyzed via CLC workbench, Ingenuity Pathway Analysis Software. Results: A total of 42 differentially expressed miRNAs were identified between intake-restriction and full-nutrition group. Among of these, mir-206, mir-133b, mir-1246, mir-1843 and mir-7139 are the most downregulated and mir-10b, mir-708 and mir-222 are the most upregulated miRNAs. A total of 1215 mRNAs were identified to differentially expressed between two groups. Two metabolic pathways: retinol biosynthesis and oxidative phosphorylation were significantly modified, and the modification was associated with the miRNA changes induced by the maternal feed restriction. Briefly, the retinol biosynthesis pathway was upregulated ( p < 0.01), in which those differential expressed mir-221, mir-4492, mir-1281 and mir-4492 were predicted targeting genes AADAC, CES3, PNPLA3 and RDH13 in the pathway. The oxidative phosphorylation pathway was upregulated ( p < 0.05), and those differential expressed mir-1843, mir-222 and mir-184 were predicted targeting genes ATP5F1C, NDUFA1, NDUFB10, and NDUFS7 in this pathway. Conclusions: These results provide the framework for further understanding of negative impact of maternal malnutrition on hepatic metabolic pathways via miRNA-RNA interactions in full-term fetal pigs. Funding Sources: Supported in part by the Bill and Melinda Gates Foundation (GCE OPP1061037) and by the North Carolina Agricultural Research Service.